PENINGKATAN KUALITAS PEMBELAJARAN IPA MELALUI MODEL PROBLEM BASED LEARNING DENGAN MEDIA AUDIOVISUAL (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2016)
The purpose of research was to improve the instructional quality of IPA (Natural Sciences) learning through Problem-based Learning (PBL) model by using audio-visual media for fifth graders of SDN Tambakaji 05 Semarang. This research design was classroom action research consisted of three cycles with four stages, namely: planning, implementing, observating, and reflection. The collecting data used test, observation, documentation, and field notes. The data were analyze using quantitative and qualitative descriptive analyze. The result showed that: (1) the teacher’s skill in the cycle I gained score 17 (good), 19 in the cycle II (very good), 22 in the cycle III (very good) ; (2) the score of students activity in the cycle I was 12.76 (good), 14.53 in the cycle II (good), 17.53 in the cycle III (good); 3) then, the learning outcome was 48.78 % in the cycle I, 68.29 % in the cycle II, and 82.93 % in the cycle III. Therefore, it can be concluded that PBL model with audio-visual media can improve the quality of natural sciences.